Impaired Platelet Function among Platelet Donors - Jilma-Stohlawetz, Petra; Hergovich, Nicole; Homoncik, Monika; Dzirlo, Larisa; Horvath, Michaela; Janisiw, Michael; Panzer, Simon; Jilma, Bernd (Thrombosis and Haemostasis, 2001)
Background: Platelet transfusions are effective for the prevention and treatment of bleeding in patients with disorders of platelet number and/or function. In recent years plateletpheresis concentrates have outnumbered pooled platelet concentrates, albeit with significant differences between nations. Thus, the platelet quality of individual donors has become increasingly important. The aim of this study was to gain an estimate for the prevalence of impaired platelet function among platelet donors. Study design and methods: We determined the inter-donor variability in platelet plug formation with a PFA-100 analyzer, the prevalence of impaired thromboxane formation, and effects of the density in alpha2 integrin polymorphism and density. Results: (i) Collagen-epinephrine induced closure time (CEPI-CT) showed a great inter-subject variability in platelet donors and was higher than in healthy controls (p = 0.008). One-fifth of donors had abnormal CEPI-CT values and 11% exceeded >300 s (max measurable value). (ii) Decreased serum thromboxane B2 levels were found in 9% of all donors, compatible with surreptitious intake of cyclooxygenase inhibitors or with an aspirin-like defect. CEPI-CT correlated inversely with TxB2-levels in donors and controls. (iii) The density of the alpha2-integrin correlated negatively with CEPI-CT and CADP-CT values in controls, but was not responsible for the observed impaired platelet function in donors. (iv) Finally, the ABO blood group system modulates closure times. Conclusion: In sum, a large number of platelet donors present with prolonged closure times. Decreased thromboxane formation and frequent platelet donation partly account for this observation.Abbreviations: 807 CC/CT/TT polymorphisms of the alpha2-integrin gene, CD36… GPIIIb, an alternative collagen receptor, CD42b… GpIb, the von Willebrand receptor, CD49b… alpha2-integrin, subunit of the main collagen receptor, CADP-CT… collagen adenosine diphosphate induced closure time, CEPI-CT… collagen/epinephrine induced closure time, PFA-100… platelet function analyzer, vWF-Ag… von Willebrand factor antigen, TXB2… thromboxane B2
Keywords: Platelet function; vWF; PFA-100; aspirin-like defect; thromboxane B2